The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/htr.0000000000000752
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association Between Childhood Trauma, Brain Injury, and Neurobehavioral Symptoms Among Survivors of Intimate Partner Violence: A Cross-Sectional Analysis

Abstract: Objective: Understanding factors contributing to neurobehavioral symptom burden among intimate partner violence (IPV) survivors has important implications for prevention, screening, and intervention in this vulnerable population. This study aimed to (1) identify the relationship between childhood trauma and neurobehavioral symptoms among a shelter-and community-based sample of IPV survivors, including investigating the mediating role of posttraumatic stress symptoms and alexithymia in this relationship; (2) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Regarding the study area, five studies were performed in Spain (Comes-Fayos et al, 2022; Mata-Gil et al, 2021; Romero-Martínez et al, 2019, 2020, 2021), four were conducted in Italy (Craparo et al 2014; Mannarini et al, 2021; Signorelli et al, 2014, 2020), three in the United States (Berke et al, 2017; Saadi et al, 2022; Yelsma, 1996), two in Australia (Brown et al, 2010; Strickland et al, 2017), one in Romania (Popa-Velea et al, 2016), one in Dominican Republic (Vergés-Baéz et al, 2021), and one in Canada (Vignola-Lévesque & Léveillée, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the study area, five studies were performed in Spain (Comes-Fayos et al, 2022; Mata-Gil et al, 2021; Romero-Martínez et al, 2019, 2020, 2021), four were conducted in Italy (Craparo et al 2014; Mannarini et al, 2021; Signorelli et al, 2014, 2020), three in the United States (Berke et al, 2017; Saadi et al, 2022; Yelsma, 1996), two in Australia (Brown et al, 2010; Strickland et al, 2017), one in Romania (Popa-Velea et al, 2016), one in Dominican Republic (Vergés-Baéz et al, 2021), and one in Canada (Vignola-Lévesque & Léveillée, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Taking all the studies together, the perpetrators of IPV amount to 837, with sample sizes ranging from 30 (Comes-Fayos et al, 2022) to 187 (Vergés-Baéz et al, 2021), whereas the victims of IPV amount to 465, with sample sizes ranging from 25 (Mata-Gil et al, 2021) to 99 (Saadi et al, 2022). Regarding sociodemographic characteristics, 781 perpetrators of IPV were male, with a mean age ranging from 33.90 (Yelsma, 1996) to 52.24 (Vignola-Lévesque & Léveillée, 2022) years, while 461 victims of IPV were female, with a mean age ranging from 31.62 (Craparo et al, 2014) to 41.55 (Popa-Velea et al, 2016) years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CTQ-SF has been used clinically both to diagnose and treat individuals with trauma (Hagborg et al, 2022;Horak et al, 2021;Nakajima et al, 2022;Rasmussen et al, 2018;Zhang et al, 2020). Scores from the CTQ-SF have been shown to positively correlate with confirmed reports of abuse, neglect, and violence (Bernstein et al, 1997;Liebschutz et al, 2018;Saadi et al, 2022). In addition, the CTQ-SF has shown good convergent validity; it has been demonstrated to correlate with, and predict risk for, interpersonal violence, posttraumatic stress disorder, depression, eating disorders, addictions, suicide attempts, personality disorders, and sexual problems (Bethell et al, 2019;Liebschutz et al, 2018;Pedrotti Moreira et al, 2018;Sacchi et al, 2018).…”
Section: Childhood Trauma Questionnaire-short Formmentioning
confidence: 99%
“…To further understand symptoms of women from a lifetime of trauma perspective, Saadi and colleagues8 examined the relations between child abuse and an IPV-related BI score reflecting neurobehavioral outcomes. They show that childhood trauma is positively associated with emotional and somatic neurobehavioral symptoms independent of BI; furthermore, they found that BI is positively associated with cognitive neurobehavioral symptoms in women who had experienced IPV-related BI.…”
Section: Increasing Our Understanding Of Neurobehavioral Symptoms In ...mentioning
confidence: 99%